2020
DOI: 10.1128/aem.02106-19
|View full text |Cite
|
Sign up to set email alerts
|

Manure Application Did Not Enrich Antibiotic Resistance Genes in Root Endophytic Bacterial Microbiota of Cherry Radish Plants

Abstract: Growing evidence suggests that livestock manure used as organic fertilizer in agriculture may lead to the potential propagation of antibiotic resistance genes (ARGs) from “farm to fork.” However, little is known about the impacts of manure fertilization on the incidence of ARGs in the plant-associated microbiomes (including rhizosphere, endosphere, and phyllosphere), which hampers our ability to assess the dissemination of antibiotic resistance in the soil-plant system. Here, we constructed a pot experiment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 51 publications
0
13
3
1
Order By: Relevance
“…The abundance of MGE was found to be positively correlated with individual ARGs coding for resistance to aminoglycoside, fluoroquinolone, quinolone, florfenicol-chloramphenicol-amphenicol, sulfonamide and tetracycline, and MDR determinants including MLSB. The results suggest that manure application significantly increased the abundance of ARGs in the rhizosphere and phyllosphere but not in the endophytes of the root, i.e., the edible part ( Zhang et al, 2020 ).…”
Section: Changes Of the Resistome In Plants Growing On Manure-fertilized Soilmentioning
confidence: 96%
See 2 more Smart Citations
“…The abundance of MGE was found to be positively correlated with individual ARGs coding for resistance to aminoglycoside, fluoroquinolone, quinolone, florfenicol-chloramphenicol-amphenicol, sulfonamide and tetracycline, and MDR determinants including MLSB. The results suggest that manure application significantly increased the abundance of ARGs in the rhizosphere and phyllosphere but not in the endophytes of the root, i.e., the edible part ( Zhang et al, 2020 ).…”
Section: Changes Of the Resistome In Plants Growing On Manure-fertilized Soilmentioning
confidence: 96%
“…A considerable number of studies have reported the presence of significant numbers of ARB on consumer-ready vegetables, such as lettuce and spinach leaves ( Abriouel et al, 2008 ; Bezanson et al, 2008 ). Zhang et al (2020) constructed a pot experiment to determine the effect of poultry and cattle manure application on resistome shifts in the plant microbiome of harvested cherry radish. A total of 144 ARGs conferring resistance to eight major classes of antibiotics were detected across all samples.…”
Section: Changes Of the Resistome In Plants Growing On Manure-fertilized Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…A pot experiment was performed in flower pots with 25 cm in height and 15 cm in diameter. The first treatment contained a total of 1.5 kg of soil with chicken manure (1 kg soil + 0.5 kg chicken manure) as a treated sample (CMR), and the other contained 1.5 kg soil without chicken manure as a control (OR) (Zhang et al 2020b). Each treatment was performed with three replicates.…”
Section: Experimental Setup and Sample Collectionmentioning
confidence: 99%
“…Estudos mostram que a disseminação de GRAs ocorre de forma intensa na rizosfera e filosfera das plantas, mas ocorre de forma mais fraca na comunidade endofítica das plantas (ZHANG et al, 2020e).…”
Section: Geração De Resíduos Agropecuários No Brasil E Seu Impacto Ambientalunclassified